Multigene Mutation Profiling and Clinical Characteristics of Small-Cell Lung Cancer in Never-Smokers vs. Heavy Smokers (Geno1.3-CLICaP) - Cardona, Andrés F.; Rojas, Leonardo; Zatarain-Barrón, Zyanya Lucia; Ruiz-Patiño, Alejandro; Ricaurte, Luisa; Corrales, Luis; Martín, Claudio; Freitas, Helano; Cordeiro de Lima, Vladmir Cláudio; Rodriguez, July; Avila, Jenny; Bravo, Melissa; et al. (Frontiers in Oncology, 2019)
Objectives: Lung cancer is a heterogeneous disease, and presentation as well as prognosis vary depending on several factors, genetic and demographic. Small-cell lung cancer is increasing in never-smokers; however, this disease entity differs from the one which presents in patients with a smoking history. Material and Methods: To further investigate the clinical and genetic characteristics of this subtype of patients, a cohort of small cell lung cancer patients were grouped into smokers (n=10) and never/ever-smokers (n=10). A somatic mutation profiling was carried out using a comprehensive NGS assay. Clinical outcomes were compared using Kaplan-Meier and Cox proportional models. Results: Median age was 63 years (46-81), 40% were men, and 90% had extended disease. Smoker patients had significantly more cerebral metastases (p=0.04) and were older (p=0.03) compared to their non-smoker counterparts. Response rates to first-line etoposide plus cisplatin or carboplatin therapy were 50% in smokers and 90% in never/ever smokers (p=0.141). Median overall survival (OS) was 29.1 months in never-smokers (95%CI 23.5-34.6) versus 17.3 months in smokers (95%CI 4.8-29.7; p=0.0054). Never/ever smoking history (HR 0.543, 95%CI 0.41-0.80), limited stage disease (HR 0.56, 95%CI 0.40-0.91) and response to first line platinum-based chemotherapy (HR 0.63, 95%CI 0.60-0.92) were independently related with good prognosis. For never/ever smokers, the main genetic mutations were TP53 (80%), RB1 (40%), CYLD (30%), EGFR (30%). Smoker patients had more RB1 (80%, p = 0.04), CDKN2A (30%, p = 0.05), CEBPA (30%, p = 0.05) mutations. Conclusion: In conclusion, our data supports that never/ever smoker patients with small-cell lung cancer have better prognosis compared to their smoker counterparts. Further, patients with never/ever smoking history who present with small-cell lung cancer have a different mutation profile compared to smokers, including a high frequency of EGFR, MET and SMAD4, which could be consequence of a diverse pathological mechanism for disease onset.